Echocardiographic and radiographic aspects of tetralogy of Fallot in a Border Collie: case report - Zardo, Karen Maciel [UNESP]; Bellota, Alexandra Frey [UNESP]; Bento, Daniel Diola [UNESP]; Souza, Priscilla Macedo [UNESP]; Oliveira, Hugo Salvador [UNESP]; Santos, Debora Rodrigues [UNESP]; Babicsak, Viviam Rocco [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Univ Federal Rural Pernambuco, 2011)
Tetralogy of Fallot is a complex cardiac malformation characterized by four anatomical defects: pulmonary valve stenosis, right ventricular hypertrophy, interventricular septal defect and aortic dextroposition. Imaging techniques are useful in the diagnosis of this disease, such as radiography for screening and Doppler echocardiography for a definitive diagnosis. Our objective is to report the radiographic and Doppler echocardiographic aspects of a tetralogy of Fallot case in a 10 month-old Border Collie dog.
Keywords: congenital heart defect; tetralogy of Fallot; dog